Assessing Canadians Health Activity and Nutritional Habits Through Social Media - Shah, Neel; Srivastava, Gautam; Savage, David W.; Mago, Vijay (Frontiers in Public Health, 2020)
When conducting data analysis in the 21st century, social media is crucial due to providing information on a variety of topics such as health, food, feedback on products, and many others. Presently, people utilize social media to share their daily lifestyles. For example, where they are going, what exercises they are doing, or what they are eating. By analyzing such information collected from these individuals, the health of the general population can be gauged. This analysis can become an integral part of a government's efforts to study the health of Canadian people on a large scale. This is because public health is becoming the primary concern for many governments around the world, and they believe it is necessary to analyze the current scenario within the population before creating any new policies. Traditionally, governments use a variety of ways to gauge flavour for any new policy including door to door surveys, National level census, or hospital information to decide health policies. This information is limited and sometimes takes a long time to collect and analyze sufficiently enough to aid in decision making. In this paper, our approach is to try to solve such problems through the advancement of natural language processing algorithms and large scale data analysis. Results show that the proposed method provides a viable solution in less time with the same accuracy when compared to traditional methods.